2017
DOI: 10.1136/heartjnl-2016-310875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin-6 inhibition on coronary microvascular and endothelial function in myocardial infarction

Abstract: Tocilizumab did not affect CFR during hospitalisation or after 6 months. Tocilizumab increased VCAM-1 levels during hospitalisation, but this was not associated with reduced CFR in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 22 publications
1
26
0
2
Order By: Relevance
“…For example, Chen et al in 1994 showed that administration of PB1.3, a monoclonal antibody to P‐selectin, reduced oxidant stress, decreased leukocyte accumulation, and preserved cardiac function in dogs subjected to ischemia‐reperfusion . However, several other studies have failed to show a beneficial effect of inhibition of inflammation in improving myocardial infarct size or cardiac function …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Chen et al in 1994 showed that administration of PB1.3, a monoclonal antibody to P‐selectin, reduced oxidant stress, decreased leukocyte accumulation, and preserved cardiac function in dogs subjected to ischemia‐reperfusion . However, several other studies have failed to show a beneficial effect of inhibition of inflammation in improving myocardial infarct size or cardiac function …”
Section: Discussionmentioning
confidence: 99%
“…26 However, several other studies have failed to show a beneficial effect of inhibition of inflammation in improving myocardial infarct size or cardiac function. 4,27 Clinical trials investigating the use of anti-inflammatory drugs in chronic heart failure have been largely unsuccessful in mitigating the process of cardiac remodeling in chronic ischemia. Inhibition of TNF-a has also been studied in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In an ischemia/reperfusion mouse model of HF, IL-6 receptor blockade resulted in neither reduced cardiac remodeling nor smaller infarct size; however, treatment was started during the acute phase, which could explain why no effects were observed [113]. Also, in humans, inhibition of IL-6 has been tested, but it was not able to improve coronary flow reserve in patients post-myocardial infarction [114]. Nevertheless, because IL-6 has been shown to be involved in HF development, and because levels of this inflammatory marker are increased in HF and are able to predict HF outcome in various types of HF [5,[115][116][117][118][119], it could serve as an HF biomarker.…”
Section: Inflammation Marker Il-6mentioning
confidence: 99%
“… Ridker et al 83 R, DB, PC 556 T2DM with high-MI risk Canakinumab 5 OR 15 OR 50 OR 150 mg 4 months CRP (+); fibrinogen (+); HbA1c (0); IL-6 (+); triglyceride (−). IL-6 inhibitors Holte et al 84 R, DB, PC 117 NSTEMI Tocilizumab 280 mg IV 6 months Coronary flow reserve (0); VCAM-1 (+) Kleveland et al 85 R, DB, PC 117 NSTEMI Tocilizumab 280 mg IV 6 months LVEF (0); SAE (0); nt-proBNP (0); Hb (0); hs-CRP (+); leukocytes (+); lipids (0); platelets (0); hs-TnT (+). Carroll et al .…”
Section: The Post-mi Immune Response As Therapeutic Target: From Fmentioning
confidence: 99%